Investigating the Elements Contributing to Self-Confidence Development in EFL Students During English Speaking - Ulthary (Barkah Publishing, 2025)
Self-confidence plays a pivotal role in determining the success of English as a Foreign Language (EFL) learners' oral communication performance. This qualitative study investigates the key determinants contributing to EFL students' lack of self-confidence during English speaking activities and outlines the strategic coping mechanisms utilized to overcome these affective and linguistic barriers. Conducted at Universitas Islam Negeri Ar-Raniry Banda Aceh, the research engaged sixth-semester English Education Department students as key informants. Data were gathered through semi-structured in-depth interviews and analyzed using an interactive qualitative analysis framework comprising data reduction, data display, and conclusion drawing. The findings reveal that students' diminished self-confidence stems from interconnected linguistic deficiencies specifically limited vocabulary, inadequate pronunciation, and weak grammatical mastery compounded by psychological constraints such as low self-belief, insecurity, and negative evaluation anxiety. To mitigate these impediments, learners employ proactive self-regulated strategies, including positive self-talk, active involvement in English-speaking communities, integration of mobile speaking applications, and sustained, deliberate speaking practice. These insights highlight the necessity for EFL educators to integrate both affective support and targeted linguistic reinforcement into speaking instruction to foster resilient and autonomous speakers.